GranDIHC-BR 2025-2035 - GC4: Sociocultural Aspects in Human-Computer Interaction - Neris, Vânia P. A.; Rosa, Jean Clemisson Santos; Maciel, Cristiano; Pereira, Vinicius Carvalho; Galvão, Vinícius F.; Arruda, Isabela L. (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2024: Anais do XXIII Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2024)
This paper addresses sociocultural aspects as a Grand Challenge for Research in Human-Computer Interaction in Brazil for 2025-2035. The challenge considers the sociocultural diversity involved in the design, implementation, evaluation, and use of interactive computational artifacts. The current scenario reveals a gap between technological solutions and the real needs of various sociocultural groups. The challenge herein described includes the creation or adaptation of tools that respect sociocultural plurality, impacting both the creation of interactive computational artifacts and the education of conscious and critical professionals. This challenge arises from the need for technologies that do not discriminate against, exclude, or harm social groups, and that are developed in a responsible, conscious, ethical, and sustainable manner. Failing to meet this challenge could lead to the formation of technological "bubbles" that promote oppressive views, diminish human capabilities, and prioritize technocapitalist interests over human concerns. In response, we suggest short-, medium-, and long-term actions, emphasizing awareness, research, and continuous monitoring. Therefore, the challenge of considering sociocultural aspects in Human-Computer Interaction aims to transform the relationship between interactive computational artifacts and society, promoting inclusion and positive impact through technological solutions that respect and represent human diversity.